Pengaruh Model Pembelajaran Read Answer Discuss Explain Create (RADEC) Terhadap Hasil Belajar IPS Siswa Kelas V SD Inpres 07 Fena Fafan - Ritiauw, Leonid; Abdurrachman, Ode; Solissa, Maya Vionita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine whether there was an effect of using the RADEC learning model on improving the social studies learning outcomes of grade V students of SD Inpres 07 Fena Fafan. The type of research used is quantitative research using pre-experimental methods and applying a one group pretest posttest design. The sample used was fifth grade students of SD Inpres 07 Fena Fafan, totalling 20 students. Data analysis techniques using descriptive statistical analysis techniques. The results showed that the use of the RADEC learning model in social studies class V SD Inpres 07 Fena Fafan for the material of the arrival of the western nation in Indonesia proved to have an effect on student learning outcomes